2020
DOI: 10.30684/etj.v38i5a.594
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Mineral Sequestration for CO2 Capturing in Car Parks and Tunnels

Abstract: Decreasing the emissions of CO2 that come from vehicle exhaust, especially in car parking and tunnels, is so vital. CO2 emissions cause corrosion to a reinforcement of concrete. Thus, there is a need to provide a layer that protects the reinforcement from the reach of this harmful gas. This work goals to investigate the efficiency of using board units from Pozzolime concrete and pervious concrete to sequestrate CO2 from the environment and then to convert it into calcium carbonate inside the concrete. The unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The majority of landfill operations do not allow the disposal of whole tires due to the size of the flames and their propensity to ascend to the surface with time. Investigations have revealed that used rubber tires contain materials that are harmful and do not disintegrate in the environment [10]. Tires can be utilized as aggregates in concrete based on these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of landfill operations do not allow the disposal of whole tires due to the size of the flames and their propensity to ascend to the surface with time. Investigations have revealed that used rubber tires contain materials that are harmful and do not disintegrate in the environment [10]. Tires can be utilized as aggregates in concrete based on these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are being urged to investigate alternatives, such as the reinstitution of lime Pozzolanic systems. Lime might be considered an ecologically friendly binder due to its low energy needs, limited CO 2 emissions during production, and carbonation-induced CO 2 uptake through setting [1]. Lime natural Pozzolans are ancient building materials that were utilized in the process of building using masonry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers are being encouraged to consider further options, one of which is the re-adopt of lime-Pozzolana systems. Lime could be regarded as an environmentally-sound binder because of its low energy requirements, minimal CO 2 emissions during manufacturing, and CO 2 preoccupation via carbonation during setting [2]. Lime-natural Pozzolana is a building material was used in masonry a long time ago [3].…”
Section: Introductionmentioning
confidence: 99%